Complex approach to skin repair in an extensively burned child: a case study. (2nd August 2020) - Zajicek, Robert; Kubok, Richard; Petrova, Nikola; Tokarik, Monika; Matouskova, Eva; Gal, Peter
Abstract : The limited amount of donor sites and loss of dermis are major challenges in the therapy of extensively burned patients. Here, we present a complex treatment approach of an eight-year-old boy with full-thickness burns on 90% of the total body surface area, using simple and efficient techniques of tissue engineering. To obtain sufficient skin for grafting we repeatedly harvested the same anatomical areas. Acceleration of donor site healing was achieved by treatment with a suspension of noncultured autologous skin cells (NASC) and acellular porcine dermis (Xe-Derma (XD), Czech Republic). Moreover, such wound management allowed up to six reharvestings, compared with one-to-three procedures following routine treatment. Bilayer Integra template (Integra LifeSciences Corp., US) was used as the dermal substitute in over 60% of full-thickness burns. Following successful vascularisation of the neodermis in 3–4 weeks, the templates were covered with meshed split-thickness skin grafts (STSG), or Meek autografts, and facilitated by NASC/XD. We may conclude that such a 'sandwich' technique approach, combining four biological covers (Integra, STSG, NASC and XD), significantly contributed to the successful skin repair of the patient.